Folic acid-modified ginger-derived extracellular vesicles for targeted treatment of rheumatoid arthritis by remodeling immune microenvironment via the PI3K-AKT pathway - Ruina Han; Dongyang Zhou; Ning Ji; Zhifeng Yin; Jian Wang; Qin Zhang; Hao Zhang; Jinlong Liu; Xinru Liu; Han Liu; Qinglin Han; Jiacan Su (Journal of Nanobiotechnology)
Abstract Rheumatoid arthritis (RA), a form of autoimmune inflammation, is marked by enduring synovial inflammation and the subsequent impairment of joint function. Despite the availability of conventional treatments, they are often marred by significant side effects and the associated high costs. Plant-derived extracellular vesicles (PEVs) offer a compelling alternative, owing to their abundant availability, affordability, low immunogenicity, high biocompatibility, and feasibility for large-scale production. These vesicles enhance intercellular communication by transferring intrinsic bioactive molecules. In our research, we delve into the capacity of PEVs to treat RA, highlighting the role of ginger-derived extracellular vesicles (GDEVs). By conjugating GDEVs with folic acid (FA), we have developed FA-GDEVs that maintain their inherent immunomodulatory properties. FA-GDEVs are designed to selectively target M1 macrophages in inflamed joints via the folate receptors (FRs). Our in vitro findings indicate that FA-GDEVs promote the polarization towards a reparative M2 macrophage phenotype by modulating the PI3K-AKT pathway. Further corroboration comes from in vivo studies, which demonstrate that FA-GDEVs not only concentrate efficiently in the affected joints but also markedly reduce the manifestations of RA. Synthesizing these findings, it is evident that FA-GDEVs emerge as a hopeful candidate for RA treatment, offering benefits such as safety, affordability, and therapeutic efficacy. Graphical abstract